FREQUENCY OF HYPERTENSIVE ENCEPHALOPATHY IN PATIENTS PRESENTING WITH HYPERTENSIVE EMERGENCY AT TERTIARY CARE HOSPITAL, KARACHI (Journal of Medical & Health Sciences Review, 2025)
Background: Hypertensive encephalopathy is a life-threatening complication of hypertensive crises, marked by impaired brain functions as a result of hypertension. It is important to be diagnosed and treated early to avoid permanent neurological disability.Objective: To establish the prevalence of hypertensive encephalopathy among patients with hypertensive emergencies at a tertiary care hospital in Karachi.Methods: The cross-sectional study was undertaken at the Department of Emergency Medicine, Jinnah Postgraduate Medical Centre, Karachi, between March and May 2025. One hundred and sixty-two hypertensive emergency patients were selected. Demographic, comorbidity, and clinical history data were gathered, and MRI brain images were taken to bring about a diagnosis of hypertensive encephalopathy.Results: Twenty-nine point six percent of patients had hypertensive encephalopathy. The prevalence rates of the comorbidities were diabetes mellitus (52.5%), dyslipidemia (55.5%), and obesity (43.2%). The frequency of encephalopathy was the most frequent in the 51-60 age group.Conclusion: One major complication of hypertensive emergencies is referred to as hypertensive encephalopathy. Comorbidities have to be addressed and managed in a timely fashion in order to improve patient outcomes.